Leave the world(view) behind, but keep the words: The effect of conspiracism on writing - Alessandro Miani; Ines Adornetti; Daniela Altavilla; Valentina Deriu; Alessandra Chiera; Francesco Ferretti (PLoS ONE, 2026)
We investigate whether a stable predisposition to interpret events as the result of conspiracies—conspiracism—is associated with the spontaneous generation of conspiratorial content in writing when interpreting ambiguous information. Across two studies ( N = 385), participants watched the apocalyptic thriller Leave the World Behind and wrote an essay interpreting its meaning. Each essay was rated by a Large Language Model for its conspiratorial narrative content, that is, the degree to which the text contains claims that the public is being pervasively lied to about aspects of reality, enabling some groups to enact a harmful, self-serving agenda. Contrary to our preregistered hypothesis, we did not find an association between participants’ conspiracism and their essays’ level of conspiratorial narrative content. Exploratory linguistic analyses revealed that conspiracism was associated with greater use of conspiracy-related vocabulary (e.g., deception, government), a disproportionate use of sophisticated words, and increased syntactic complexity. These results suggest that conspiracism may emerge more readily at the lexical level rather than through fully structured narratives. We discuss potential methodological and theoretical factors contributing to these unexpected results, including the roles of context, perceived relevance, motivation, and collective social dynamics. We also consider the possibility that conspiracism may not directly translate into conspiratorial narratives. If so, we recommend comparative research on online vs offline conspiratorial writing to clarify whether conspiracy theories emerge spontaneously from genuine beliefs or are constructed strategically, detached from genuinely held beliefs.